Hacker News new | past | comments | ask | show | jobs | submit login

https://en.wikipedia.org/wiki/Logical_biconditional

(A⇔B)⇔C has more in common with the other logical operators: due to it's associativity an interpretation that is, in my opinion, closer than A=B=C.

Edit, removed: Note that (A⇔B)∧(B⇔C)) is not one of the two ambiguous options: either (A⇔B)⇔C or (A∧B∧C)∨(¬A∧¬B∧¬C) this is wrong.




What? `(A⇔B)∧(B⇔C)` is exactly equivalent to `(A∧B∧C)∨(¬A∧¬B∧¬C)` which is equivalent to `A = B = C`


So it is.




Consider applying for YC's Spring batch! Applications are open till Feb 11.

Guidelines | FAQ | Lists | API | Security | Legal | Apply to YC | Contact

Search: